Kelayakan Masker Mentimun Dan Tepung Beras Untuk Mencegah Kulit Berjerawat - Zahra Zegita; Rahmiati (Universitas Negeri Jakarta, 2024)
Cucumber is a type of vegetable that can be used as a basic ingredient for making masks. Cucumbers can be used as a cool, refreshing ingredient, a cleanser, a moisturizer, and for acne-prone skin care. To prevent acne-prone skin, you can use a mask made from natural ingredients, namely, cucumber mixed with rice flour. Cucumbers contain many vitamins, such as vitamin A and vitamin C, while rice flour contains gemma oryznol, which is effective in forming melanin pigment, acting as an antioxidant and protecting against ultraviolet rays. This study aims to test the suitability of a cucumber and rice flour mask for preventing acne. The research method used is a quantitative experiment. By carrying out organoleptic tests and hedonic tests. The data analysis technique in this research uses percentages. Based on the research results, the panelists' preferences indicated that a mask made from cucumber and rice flour was suitable for preventing acne-prone skin.